Screening for Collusion: A Spatial Statistics Approach - Pim Heijnen; Marco A. Haan; Adriaan R. Soetevent (Tinbergen Institute, 2012)
We develop a method to screen for local cartels. We first test whether there is statistical evidence of clustering of outlets that score high on some characteristic that is consistent with collusive behavior. If so, we determine in a second step the most suspicious regions where further antitrust investigation would be warranted. We apply our method to build a variance screen for the Dutch gasoline market.
Keywords: C11; D40; L12; L41; 330; collusion; variance screen; spatial statistics; K-function